The Effectiveness of Project-Based Learning in a Skirt Making Skill for Deaf Students - Firma Dina; Jon Efendi (STAI Miftahul Ula Nganjuk, 2020)
Starting from the preliminary study conducted by the authors at the SLB Perwari and found the condition where the deaf students of grade X have not been able to make a skirt that became one of the materials in the vocational learning curriculum for the class, one of his students is the teacher has not found and used the right method to teach the material. Then the author is motivated to prove one of the methods of learning, which is a project-based learning method, whether the method has an effect on learning the material. With experimental research methods and pre-experimental design of one group pre-test post-test, the author performs a stage of research starting from the initial test, then administering the treatment, then the final test. While the tools used in collecting data is a proven instrument that is valid and reliable. The results of the initial test scores and the final tests were then calculated by statistical tests using Wilcoxon's signed ranks test (Wilcoxon matched pairs) formula and the resulting results where the value of ASYMP. The Sig. (2-tailed) is smaller than the significant level value